åˆ©ç”¨åŒä¼´æ•™å¦æ³•æé«˜LKIAä¸ä¸“äºŒå¹´çº§å¦ç”Ÿæ±‰è¯è¯æ±‡å¦ä¹ çš„èƒ½åŠ› - Nurjannah, Nurjannah; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe main purpose of this paper is to understand how to use peer teaching in a real teachingÂ-learning experience, to understand the peer teaching-learning method can increase studentâ€™s ability in learning Mandarin vocabulary. The subject of this research is the eleventh grade of SMK LKIA for accounting major. The method used in this research is classroom action research , research method , test method and comparison method.Based on the result , the researcher found that peer teaching has increased studentâ€™s motivation in the class.This method also helps studentâ€™s to understand Mandarin vocabulary. Besides using Â peer teaching learning method in teaching learning process stimulates students , moreover , peer teaching increases studentâ€™s interest in learning, increases score, confidence and makes student easier to get teaching learning strategy of â€œpeerâ€ . Thus, the students have got a good improvement during learning process.